An Assessment Of Service Quality In Gunung Mulu National Park - Said, Abas; S , Ahmad; Y, Fazlina (2009)
This paper highlights the results of a study on service quality conducted in Gunung Mulu National Park (GMNP), Sarawak. National parks in Sarawak are established and managed to advocate protection and conservation of the forest resources and essential environmental services. These national parks are becoming popular among ecotourists and recreationists to experience nature and enjoy nature-based activities. Ecotourism provides opportunities for visitors and local communities to increase their awareness and to support and appreciate efforts in conservation and protection of natural resources. It can also potentially benefits local communities through creation of employment opportunities and as an alternative source of income. Thus, understanding service quality is vital to improve visitors' experience and satisfaction as well as to sustain benefits of ecotourism to local communities. The ECOSERV instrument developed by Khan in the United States was utilized to assess service quality from visitors' perspectives. A survey of visitors using a questionnaire set was conducted to evaluate visitors' perceptions and expectations regarding service quality in GMNP. The gaps between visitors' perceptions and expectations were analyzed to determine the satisfactory level of visitors with services provided in GMNP. Significant results obtained are discussed and recommendations put forward to improve services and management of GMNP.